2018
DOI: 10.1080/01402382.2018.1479921
|View full text |Cite
|
Sign up to set email alerts
|

Why do only some people who support parties actually join them? Evidence from Britain

Abstract: What makes people join a political party is one of the most commonly studied questions in research on party members. Nearly all this research, however, is based on talking to people who have actually joined parties. This article simultaneously analyses surveys of members of political parties in Britain and surveys of non-member supporters of those same parties. This uniquely enables us to model the decision to join parties. The results suggest that most of the elements that constitute the influential 'General … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 16 publications
3
27
0
3
Order By: Relevance
“…However, clearly the most common motivation among party joiners is to express support for party aims, values and policies (purposive, collective or expressive incentives), often combined with a belief in contributing to the democratic process (a form of altruism) (Bale et al, 2020: 79). The dominance of these incentives -support for party principles and policies -appears close to universal in party membership studies (Cross and Young, 2002;Mitchell et al, 2012;Poletti et al, 2019;Whiteley et al, 2019).…”
Section: Referendums Parties and Movementsmentioning
confidence: 84%
“…However, clearly the most common motivation among party joiners is to express support for party aims, values and policies (purposive, collective or expressive incentives), often combined with a belief in contributing to the democratic process (a form of altruism) (Bale et al, 2020: 79). The dominance of these incentives -support for party principles and policies -appears close to universal in party membership studies (Cross and Young, 2002;Mitchell et al, 2012;Poletti et al, 2019;Whiteley et al, 2019).…”
Section: Referendums Parties and Movementsmentioning
confidence: 84%
“…Drawing on incentives theory, we have shown that two things are critical in the context of single-member district contests: the aspiration to become an elected politician, and becoming involved in a social network based around the local constituency party community. While purposive incentives such as ideological or policy preferences certainly help explain why people join parties in the first place (Poletti et al, 2019) and engage in low-intensity party work, the desire to become a politician (which only accounts for a small number of members) or local social network involvement play a far greater role in persuading people to commit much of their time to high-intensity campaign activity. The greater the time spent on such activity, and the higher the intensity, the more that political career ambition and social networking matter.…”
Section: Resultsmentioning
confidence: 99%
“…One way to get a better idea of what strategies might work would be to establish whether men and women partisans have differing perceptions of the costs or benefits of party membership and party activism (putting a gendered focus on studies along the lines of Poletti et al. (2019) or the chapters in van Haute & Gauja (2015)). But even if more research is needed to identify plausible specific remedies, what does seem clear from the results presented here is that parties should not count on closing the grassroots participation gap merely by using the tools that have promoted women's access to elite levels of the party.…”
Section: Discussionmentioning
confidence: 99%